Deep analysis of the solubility behaviour mechanism of alpha-(trichloromethyl) benzyl acetate in three binary aqueous solvents. (December 2020) - Wei, Ning; Shang, Zeren; Zhang, Nuoyang; Wang, Jingkang; Wu, Songgu
Graphical abstract: Crystallographic structure analysis and σ-profile analysis were used to reveal the dissolution thermodynamic behavior of alpha-(Trichloromethyl) benzyl acetate. In the in-depth study of the dissolution thermodynamic behavior in binary mixed solvents of water and acetic acid halogen bonds generate in the solution. After comparing the σ-profile of acetic acid and isopropanol it is confirmed that the formation of halogen bonds with ATMBA molecule is the acetate ion rather than the acetic acid molecule. This causes the phenomenon that violate the principle of "like dissolves like" in the binary mixed solvents of acetic acid and water. Subsequently the experimental verification proves that the theory is indeed credible. Highlights: Solubility of ATMBA was measured by static method in three binary mixed solvents. Thermodynamic analyses were performed based on functions of mixing. σ-profile analysis was used to reveal the solubility behavior mechanism of ATMBA. It is the acetate ion that forms halogen bonds with ATMBA molecule. The molecular dynamic simulation and experiments were used to verify the analyses. Abstract: The solubility of alpha-(Trichloromethyl) benzyl acetate (ATMBA) in three water-organic binary solvent mixtures at atmospheric pressure from 288.15 K to 328.15 K was investigated by the gravimetric method and molecular simulations. The experimental solubility data were well correlated by the modified Apelblat model Van't Hoff equation and the NRTL model. In addition calculations of the mixed thermodynamic properties indicate that the mixing process of ATMBA in the solvent systems studied is exothermic and spontaneous. Further to reveal the solubility behaviour of ATMBA thermodynamic analysis crystallographic structure analysis and σ-profile analysis were applied. After comprehensive analysis we found that the reason of the abnormal solubility of ATMBA in acetic acid is that in the binary solvent of acetic acid and water the solute (ATMBA) forms a strong halogen bond with the ionized acetic acid (acetate ion). Finally we validate the rationality of the above analysis process by dynamics simulation (MS). And the Radial distribution function (RDF) shows that it is indeed possible to form a halogen bond between the solute and the acetate ion. Subsequently under the guidance of this theory the binary mixed solvents of formic acid and water were used for experimental verification and the results showed an excellent solubility tendency which proved that the theory is indeed credible. The experimental data can be used as basic data in the industrial production and scientific research of ATMBA a high value-added product. Thermodynamic analysis crystallographic structure analysis σ-profile analysis MD simulations and correlation models herein are helpful to a further understanding of solid–liquid equilibrium of compounds in binary solvent systems.